Angiotensin-Converting Enzyme Genotype–Specific Immune Response Contributes to the Susceptibility of COVID-19: A Nested Case–Control Study - Gong, Pengyun; Mei, Fanghua; Li, Ruili; Wang, Yuchen; Li, Weizheng; Pan, Kai; Xu, Junqiang; Liu, Chao; Li, Hongjun; Cai, Kun; Shi, Wei (Frontiers in Pharmacology, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease 2019 (COVID-19), which has resulted in a global pandemic. Methodology: We used a two-step polymerase chain reaction to detect the ACE genotype and ELISA kits to detect the cytokine factor. We also used proteomics to identify the immune pathway related to the ACE protein expression. Result: In this study, we found that the angiotensin-converting enzyme (ACE) deletion polymorphism was associated with the susceptibility to COVID-19 in a risk-dependent manner among the Chinese population. D/D genotype distributions were higher in the COVID-19 disease group than in the control group (D/D odds ratio is 3.87 for mild (p value < 0.0001), 2.59 for moderate (p value = 0.0002), and 4.05 for severe symptoms (p value < 0.0001), logic regression analysis. Moreover, genotype-specific cytokine storms and immune responses were found enriched in patients with the ACE deletion polymorphism, suggesting the contribution to the susceptibility to COVID-19. Finally, we identified the immune pathway such as the complement system related to the ACE protein expression of patients by lung and plasma proteomics. Conclusion: Our results demonstrated that it is very important to consider gene polymorphisms in the population to discover a host-based COVID-19 vaccine and drug design for preventive and precision medicine.